Penggalian Potensi Perluasan Basis Pajak Daerah Provinsi Jawa Barat Dalam Menghadapi Pandemi Covid-19 - Dwikora Harjo (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2021)
The Covid-19 pandemic that has hit Indonesia since March 2020 had a significant impact on the economy around the world, including West Java. The Regional Revenue Agency (Bapenda) of West Java as the regional financial manager must be proactive in looking for innovations to obtain new tax objects in dealing with additional funds for handling this pandemic, one of them is to propose a new Regional Tax object which called Rainfed Tax. With a descriptive qualitative method through a literature study, an analysis of the exploration of potential local tax objects in this pandemic period was carried out. Rainfed Tax is imposed on protected owners of buildings and facilities / infrastructure that cover land as rainwater infiltration, which is an Earmarking Tax that regulated in a Regional Regulation or Governor's Decree of West Java. Even though it is in the Earmarking Tax category with the aim of financing the construction of rainwater storage places to avoid frequent floods and landslides, the revenue from this Rainfed Tax, with the approval of legislators, can be done switching to finance the covid-19 pandemic response in West Java. The potential for rainfed tax in West Java is very high, this is supported by the large number of buildings / properties in the form of buildings along with facilities and infrastructure that cover the ground for rainwater absorption.